P255 Limitations of a community calprotectin service and outcomes from patients tested outside of an approved pathway. (16th January 2018) - James, L; Gama, R; Ford, C; McKaig, B; Whitehead, S; Pelitari, S; Steed, H; Brookes, M
Abstract: Background: In 2014, we developed a successful virtual clinic for assessment of all new Gastroenterology referrals to secondary care, which face to face clinics by approximately 32%. This included a diarrhoea referral pathway, aligned to community faecal calprotectin (f-Cp) testing. The service was set up to allow community physicians to access f-Cp to screen for new cases of IBD in line with UK practice guidance (NICE). Community practices were advised to only test for f-Cp within the agreed care pathway; patients under 45 years age, diarrhoea symptoms for >6 weeks, no alarms symptoms (abdominal mass, rectal bleeding, weight loss or anaemia). Methods: Retrospective analysis of our electronic clinical chemistry calprotectin database over a 27-month period between October 2014 and December 2016. Data collected included demographics, f-Cp results, subsequent investigations (endoscopic, imaging), and outcomes (clinic attendance, diagnosis). Results: Over a 27 month period our new pathway generated 1662 f-Cp sample requests from community clinicians. 2.7% ( n = 46) had no results and/or could not be analysed (analytical error, insufficient sample). Between 35% ( n = 587/1662; anaemia) and 29% ( n = 480/1662; rectal bleeding) had incomplete clinical data provided. Complete forms with all clinical data were provided for 63% of requests ( n = 1051/1662). Inappropriate samples (outside the recommended pathway) were received in the following categories: i) 31% ( n = 363/1182) with diarrhoea < 6weeks; ii) 33% ( n = 554/1662) age >45 years; iii) 4% (48/1075) anaemia was present; iv) 0.69% (8/1162) rectal or abdominal mass was known; v) 10% (113/1181) rectal bleeding present. For 33% ( n = 554/1662) of samples patients were aged >45 years and several of these were tested on multiple occasions (554 samples in 489 patients). In the over 45 aged cohorts 4.29% of patients ( n = 21/489) had known inflammatory bowel disease (IBD) and 0.2% ( n = 1/489) were newly diagnosed with IBD. In the over 45 aged cohort of patients excluding those with known IBD ( n = 21), the new case of IBD ( n = 1) and error data ( n = 4) we found that the following investigations were undertaken; radiology in 20% ( n = 93/463); stool for microbiology in 41% ( n = 187/461); colonoscopy in 40% ( n = 182/459). Conclusions: Despite the success of the development of a virtual clinic and a pathway for managing patients with diarrhoea, we have seen larger numbers of inappropriate requests for f-Cp testing. In patients over the age of 45 years false reassurance may prevent onwards referral for further investigation. Only one patient in this cohort was found subsequently to have IBD. Community calprotectin screening in patients aged over 45 years does not help to identify patients with IBD and should be discouraged.